Genetic improvement and molecular characterisation of paprika(capsicum annuum L.) genotypes - Bini Philip (Department of Plant Breeding and Genetics, College of Agriculture, 2004)
Chilli (Capsicum annuum L.) is an important spice cum vegetable crop yielding capsaicin, oleoresin and natural colour besides green and dry fruits. Paprika belonging to Capsicum annuum is characterised by good colour and low pungency can be used both as vegetable and spice. The increasing commercial importance world over for paprika as sources of paprika powder and oleoresin has resulted in establishing breeding programmes to develop varieties or hybrids to meet domestic as well as export demands. The present investigation entitled “Genetic improvement and molecular characterization of paprika (Capsicum annuum L.) genotypes” conducted at the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during 2002-2004 was given prime importance for the development of improved chillies with paprika quality through hybridization. Chilli germplasm consisting of 44 genotypes were evaluated for yield traits and quality characters and considerable variations were observed among genotypes for 16 traits viz., days to 50 per cent flowering, plant height, primary branches per plant, secondary branches per plant, fruits per plant, fruit length, fruit girth, fruit weight, seeds per fruit, 100 seed weight, crop duration, yield per plant, ascorbic acid content, oleoresin content, capsanthin content and capsaicin content. The maximum values of both phenotypic and genotypic coefficients of variation were noticed for yield per plant and fruits per plant. All the traits exhibited high heritability especially yield per plant and fruits per plant. Genetic advance as per cent of mean was found high for all the characters except days to 50 per cent flowering for which it was moderate. Correlation analysis indicated significant positive correlation of yield per plant with fruits per plant, fruit length, fruit weight, 100 seed weight, plant height, oleoresin content, ascorbic acid content and crop duration and negative correlation with days to 50 per cent flowering. Negative correlation was observed between capsanthin content and capsaicin content. Selection indices were computed based on 16 traits and genotypes were ranked accordingly. Genotypes were grouped into nine clusters based on Mahalanobis D2 statistic. Based on the selection index and quality parameters seven genotypes viz., EG-85, Vellayani local, Jwalamukhi, Kattakkada local, Kaliyikkavila local, EG-101 and Arka Abir were selected from different clusters as parents for hybridization. Half diallel analysis revealed predominantly non-additive gene action for most of the characters but additive gene action was found for fruit length and fruit girth. On the basis of gca effects and mean performance Arka Abir was the best parent for quality characters and Vellayani local for yield related characters. Among the 21 hybrids evaluated with respect to mean performance, standard heterosis and sca effects P1 x P7 (EG-85 x Arka Abir) was superior with respect to earliness, capsanthin content, low pungency, fruit length and oleoresin content. For yield attributes two hybrids can be projected as superior ones. The hybrid Vellayani local x EG – 101 performed best for yield per plant, fruit weight, primary branches per plant, secondary branches per plant and fruits per plant. Vellayani local x Kattakkada local showed best performance for plant height, fruits per plant, yield per plant, fruit weight, oleoresin content and ascorbic acid content. Comparative study on green fruit yield per plant, ripe fruit yield per plant, dry fruit weight recovery and pericarp thickness revealed high positive correlation between green fruit yield and ripe fruit yield per plant and negative correlation between pericarp thickness and dry fruit weight recovery. Maximum dry fruit weight recovery was for the hybrid EG-85 x Arka Abir. RAPD analysis was performed using the random primer OPA-10 and the 28 genotypes including seven parents and 21 hybrids were characterized using Jaccard’s similarity coefficient analysis and a dendrogram was constructed to cluster the genotypes. The superior hybrid with respect to paprika quality EG-85 x Arka Abir was characterized using three random primers and its hybridity was proved.